Jane Austen, scrittrice professionista nel periodo della Reggenza - Sabrina Panin (Annali Online dell'Università di Ferrara. Sezione Lettere, 2019)
The paper aims to discuss the publishing system during the Regency and more precisely Jane Austen’s publications. The text is divided into three parts. The first one deals with women writers’ conditions and the obstacles that they have to overcame in order to publish their manuscripts. The second part is about the different types of publication available during the Regency and the last one follows Jane Austen’s career and the difficulties she has suffer to publish her novels. The study is based upon the information taken from scholar’s studies, Jane Austen’s books and letters, and also from the biographical anecdotes about her life that her siblings have written.